ZONA POTENSIAL PENANGKAPAN IKAN (FISHING GROUND) MENGGUNAKAN CITRA SATELIT TERRA MODIS DI PANTAI BARAT KABUPATEN MANDAILING NATAL - Nurul Maidah Nasution; Widya Prarikeslan (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
The purpose of research is to look at sea level temperature, chlorophyll-a concentration, the connection between sea level temperature and chlorophyll-a as well as potential zone of fishing in June, July and August based on the last 3 year data using fashionable Terra Modis. The method used is an Overlay analysis between sea level temperature, chlorophyll-a concentration by looking at the depth factor and considering the fishing pathway. The result obtained by the sea surface temperature have a spread of between 27,1oC – 32,2oC, Usually the june temperature is higher that in July and August reaches 32,2oC in 2018. Chlorophyll-a ranges from 0,1 – 6,2 mg/m3 with hight concentrations of chlorophyll-a Juny. Analysis of sea surface temperature relations with chlorophyll-a through simple linear regresion, there is a strong influence between sea level temperatures to chlorophyll-a visible coeffcient of correlation (R) 0.826, coefficient of determination (R2) 0.683 which means the sea level temperature on the Pantai Barat Natal affects the chlorophyll-a of 63,8% the rest is influenced by other factors. The fishing ground may occur in the Ib zone until zone II of the DPPI. Keywords: terra modis; sst; chlorophyll-a; mackerel; fishing ground